An intercomparison of the thermal offset for different pyranometers. Issue 13 (4th July 2016) - Sanchez, G.; Cancillo, M. L.; Serrano, A.
Abstract: An unprecedented intensive intercomparison campaign focused on the experimental measurement of the thermal offset of pyranometers has been conducted at Badajoz (Spain) with the participation of three main manufacturers. The purpose of this study is to compare the thermal offset of six commercially available pyranometers, being some of them widely used and others recently commercialized. In this campaign, the capping methodology has been used to experimentally measure the daytime thermal offset of the pyranometers. Thus, a short but intense campaign has been conducted in two selected summer days under clear‐sky conditions, covering a large range of solar zenith angle, irradiance, and temperature. Along the campaign, a total of 305 capping events have been performed, 61 for each pyranometer. The daytime thermal offset obtained for different pyranometers ranges between 0 and −16.8 W/m 2 depending on the environmental conditions, being sometimes notably higher than values estimated indoors by manufacturers. The thermal offset absolute value of all instruments shows a diurnal cycle, increasing from sunrise to central hours of the day and decreasing from midafternoon to sunset. The analysis demonstrates that thermal offset is notably higher and more variable during daytime than during nighttime, requiring specific daytime measurements. Main results emphasize the key role played by wind speed in modulating the thermal offset. Key Points: First intensive intercomparison campaign of pyranometer thermal offset with the main manufacturers Daytime thermal offset differs between instruments, ranging mostly between 0 and ‐10 W/m² Daytime thermal offset in clear skies shows a diurnal cycle being wind speed a key factor